Midterm Examination: Economics 210A
October 2011
The exam has 6 questions. Answer as many as you can. Good luck.
1) A) Must every quasiconcave function must be concave? If so, prove it. If not,
provide a counterexample. (In all answers where you provide a counterexample,
you must show that your example is really a counterexample.)
Answer:
Not every quasiconcave function is concave. Here is
ac
oun
t
e
r
ex
amp
l
e
. D
eFn
eth
efun
c
t
i
on
F
with domain
°
+
(the
positive real numbers.) such that
F
(
x
)=
x
2
.W
eshowtw
oth
ing
s
:
1) This function is quasiconcave.
1
To see this, note that
F
is a
strictly increasing function on
°
+
.The
re
fo
rei
f
F
(
y
)
≥
F
(
x
), it must
be that
y
≥
x
and hence for any
t
∈
[0
,
1],
ty
+(1
−
t
)
x
≥
x
.S
in
c
e
F
is an increasing function, it follows that
F
(
ty
+(1
−
t
)
x
)
≥
F
(
x
)
.
Therefore
F
is quasiconcave. 2) The function
F
is not concave. To
see this, note that
F
(2) = 4 and
F
(0) = 0, but
F
(
1
2
2+
1
2
0) =
F
(1) = 1
≤
1
2
F
(2) +
1
2
F
(0) = 2
.
This cannot be the case if
F
is a concave function.
B) Must every concave function be quasiconcave? If so, prove it. If not, provide
a counterexample.
Answer:
Every concave function is quasiconcave. Proof. If
f
is
concave, its domain is a convex set
A
.±
o
ra
l
l
x
and
y
in
A
,and
t
between 0 and 1, if
f
(
tx
+(1
−
t
)
y
)
≥
tf
(
x
)+(1
−
t
)
f
(
y
)
.
(1)
±rom the Expression
??
it follows that
f
(
tx
+(1
−
t
)
y
)
≥
f
(
y
)+
t
(
f
(
x
)
−
f
(
y
))
.
(2)
If
f
(
x
)
≥
f
(
y
), then it follows from Expression
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document2) Let
F
and
G
be realvalued concave functions with the same domain,
A
.
DeFne the function
H
so that for all
x
∈
A
,
H
(
x
)=
F
(
x
)+
G
(
x
). Is
H
a
concave function? If so, prove it. If not, provide a counterexample.
Answer:
Since
F
and
G
are concave functions with domain
A
,it
must be that if
x
∈
A
and
y
∈
A
,thenfora
l
l
t
between 0 and 1,
F
(
tx
+(1
−
t
)
y
)
≥
tF
(
x
)+(1
−
t
)
F
(
y
)
and
G
(
tx
+(1
−
t
)
y
)
≥
tG
(
x
)+(1
−
t
)
G
(
y
)
Given these two inequalities, we see that
H
(
tx
+(1
−
t
)
y
)=
F
(
tx
+(1
−
t
)
y
)+
G
(
tx
+(1
−
t
)
y
)
≥
tF
(
x
)+(1
−
t
)
F
(
y
)+
tG
(
x
)+(1
−
t
)
G
(
y
)
=
t
(
F
(
x
)+
G
(
x
)) + (1
−
t
)(
F
(
y
)+
G
(
y
))
=
tH
(
x
)+(1
−
t
)
H
(
y
)
By deFnition, the left side of Expression
??
equals
H
(
tx
+(1
−
t
)
y
).
The right side of Expression
??
equals
tF
(
x
)+
tG
(
x
)+(1
−
t
)
F
(
y
)+
(1
−
t
)
G
(
y
)=
tH
(
x
)+(1
−
t
)
HY
). Therefore
H
(
tx
+(1
−
t
)
y
≥
tH
(
x
)+(1
−
t
)
H
(
y
)
for all
t
between 0 and 1, which means that
This is the end of the preview. Sign up
to
access the rest of the document.
 Fall '09
 Bergstrom
 Economics

Click to edit the document details